Integrasi Pembinaan Spiritual dan Edukasi Anak Usia Dini melalui Kegiatan PKL di Masjid dan TK Muhammadiyah Tegalharjo, Surakarta: Integration of Spiritual Development and Early Childhood Education through Fieldwork Activities at the Mosque and Muhammadiyah Kindergarten in Tegalharjo, Surakarta - Dhini Sri Utami; Azizah Suci Agustin; Puan Maharani Ariel Palasthree Ulil Amri; Fitri Ramadhani Purnomo; Nancy Eka Setiawati; Savna Cindy Claudia; Zaandya Fauziah Nur Hidayat; Ahmad Nurrohim (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This Community Service activity aims to integrate spiritual development and early childhood education through Field Work Practice (PKL) activities carried out at the Muhammadiyah Tegalharjo Mosque and Kindergarten, Surakarta. Based on the situation analysis, there are still limitations in strengthening spiritual values ​​and learning methods that are fun and appropriate for children's development. The problems faced include the lack of an integrated approach between religious education and early childhood cognitive development. Activity methods include observation, interviews, designing integrated learning programs, implementing educational activities such as Islamic thematic learning, play while learning activities, and strengthening character through exemplary stories and the habit of daily worship. The results of the activity show an increase in children's enthusiasm in participating in spiritual and learning activities, as well as an increase in teacher involvement in implementing a holistic approach. The discussion shows that an integrative approach between spiritual and early childhood education is effective in instilling moral values ​​and a love of religious activities from an early age. This activity also has a positive impact on increasing teacher capacity in designing meaningful and contextual learning. In conclusion, the integration of spiritual formation and early education through PKL activities can be an alternative model of values ​​and character-based learning for early childhood education institutions.